Tafsir al-Qur'an dengan al-Sunnah - Ansori, Isa (KALAM, 2017)
This paper focuses on describing the interpretation of al-Qur’an with al-Sunnah. The use of sunnah or hadith for the interpretation of the Qur'an can be seen from several aspects, from the aspect of the assessment of the contents of the texts, it is distinguished into, first, using the sunnah or hadith which its contents directly affects the Qur'an, or second, using the sunnah or hadiths that are useful for supporting interpretation although the content of the texts has no direct relation to lafaz or verse being interpreted. In addition, the sunnah or hadith also can be seen from its function in explaining lafaz or verse, explaining topics such as fiqh, tasawuf, history etc., explaining etymology, snatching, asbāb al-nuzul support, and other uses that may be found along with the development of science. While in the study of Islamic jurisprudence, the position of sunna against the Qur'an has an important function as bayān al-taqrīr, bayān al-tafsīr which includes tafṣil al-mujmāl, takhṣiṣ al-'ām, taqyid al-muṭlaq, also bāyan al-tashrī ', bāyan al-nasakh and defines the mubham.